Endoscopy for removal of foreign body in Red-Footed-Tortoise (Chelonoidis carbonaria): Case report - Curi, Nelson Henrique de Almeida; Mattoso, Luana Martins Machado; Araújo, Rafaella D’ávila Milioreli; Leite, Leandro Souza (Pubvet, 2024)
Endoscopy offers multiple applications for Veterinary Medicine of non-domestic species, and its use is growing in the country. Among the most raised species as non-conventional pets, the red-footed-tortoise (Chelonoidis carbonária) is a reptile with terrestrial habits and prone to ingestion of strange bodies, such as stones and metallic objects. However, the present report describes a case of accidental iatrogenic ingestion of a feeding probe by a tortoise, and the procedure that included partial intravenous anesthesia and video-endoscopy for location and removal of the foreign body.
Keywords: Anesthesia; wildlife animals; endoscopium; chelonians